The Impact of Export Import on the Macro Economy - Maryam Batubara; Sibral Malasyi (Institut Agama Islam Al-Aziziyah Samalanga, 2023)
This article aims to determine the effect of international trade, namely the ratio of export and import growth in both the oil and gas and non-oil and gas sectors, as well as the amount of investment that is included in the FDI category on economic growth in Indonesia. The object in this paper is focused on all variable data for 2012 -2019, with the data used is quarterly data. This article also involves the inflation rate which is then used as a control variable. as a whole proves that exports and investment have a significant positive effect on economic growth while the amount of imports has a significant negative effect on economic growth.